Assessment of Factors That Contribute to Bladder Cancer - mohammed, Khalida; Al- An, Betool (Iraqi National Journal of Nursing Specialties, 2005)
Abstract Objective: The study aimed to assess the factors contributes of patient with bladder cancer and to find out the relationship between the factors of bladder cancer with certain variable. Methodology: A descriptive study to assessment of factors that contribute to bladder cancer that was carried out Al-Karama teaching hospital, Al-Kendy teaching hospital, Specialty Surgery teaching hospital and Al-Yarmok teaching hospital for the period of November 2003 to August 2004. A purposive (non-probability) sample of (100) patients with bladder cancer. An assessment from was constructed for the purpose of the study. It comprised of two parts, which were dealing with the demographic information sheet, and factors contribute. Test- retest reliability was employed through computation of Pearson correlation coefficient. Content validity of assessment form was determined through a panel of experts and pilot study. Data were collected through the application of the questionnaire and interview technique. The assessment was conducted during the period (10th) March 2004 to (5th) August 2004. Data were analyzed through descriptive statistical approach. Result: The study concluded that the age over (50) years, majority of them was male, married, they had low level education, and most of them were smoking and drinking tea. Recommendation: The study recommended that to stop smoking and establishing specialized center of bladder cancer in Iraq. Key wards: Factors, Bladder cancer